1991
DOI: 10.1177/014272379101103305
|View full text |Cite
|
Sign up to set email alerts
|

Maltreated children's language and speech development: abused, neglected, and abused and neglected

Abstract: Seventy-four preschool-age maltreated children's receptive and expressive language, speech skills, general language and cognitive abilities were assessed to investigate the language, speech and cognitive skills of abused, neglected, and abused and neglected children. While all three groups were delayed, neglect was the type of maltreatment most strongly associated with both expressive and receptive language delays and overall language delay. The three groups did not differ in general cognitive development. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 24 publications
3
54
0
4
Order By: Relevance
“…Another study assessed language development in 74 maltreated preschoolers, comparing those neglected only, physically abused, or both neglected and physically abused (Culp et al, 1991). Their results showed that children only neglected performed significantly worse on language assessment than those physically abused or both neglected and physically abused.…”
Section: Interactive Model Of Risk With Multiple Maltreatmentmentioning
confidence: 99%
“…Another study assessed language development in 74 maltreated preschoolers, comparing those neglected only, physically abused, or both neglected and physically abused (Culp et al, 1991). Their results showed that children only neglected performed significantly worse on language assessment than those physically abused or both neglected and physically abused.…”
Section: Interactive Model Of Risk With Multiple Maltreatmentmentioning
confidence: 99%
“…Neuropsychological studies link childhood neglect with particularly adverse outcomes in relation to auditory attention, verbal comprehension, performance on verbal and nonverbal subtests of IQ batteries, and mental inflexibility (see Nolin & Ethier, 2007, for review). Specific linguistic sequelae have also been described (e.g., by Coster & Cicchetti, 1993;Culp et al, 1991;McFadyen & Kitson, 1996) in sub-populations of maltreated children. Deficits described include delayed syntactic development, reduced vocabulary size, poor auditory comprehension skills and pragmatic impairments.…”
Section: The Neurobiology Of Child Maltreatmentmentioning
confidence: 99%
“…Ultimately, a history of childhood traumatic experiences raises the risk for adverse outcomes, including substance use and abuse, teen pregnancy and paternity, suicidality and other self-injurious behaviors, criminal activity, and re-victimization (Anda, 2002 (Egeland, Sroufe, & Erickson, 1983). The sensory and emotional deprivation associated with neglect appears to be particularly detrimental to development, with neglected infants and toddlers demonstrating delays in expressive and receptive language development, as well as deficits in overall IQ (Allen & Oliver, 1982;Culp, Watkins, Lawrence, Letts et al, 1991;Vondra, Barnett, & Cicchetti, 1990). Over time, these decrements in cognitive ability continue to be observed, such that abused and neglected children show lower IQ's and are disproportionately represented within the developmentally delayed spectrum of intellectual functioning (Sandgrund, Gaines, & Green, 1974).…”
Section: Dissociation Dissociation Dissociation Dissociation Dissociamentioning
confidence: 99%